1979
DOI: 10.1139/v79-444
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the determination of the relative acidities of alcohols in alcoholic solutions. The nucleophilicities and competitive reactivities of alkoxides and phenoxides

Abstract: A new semiquantitative method has been developed for measuring the relative acidities of methanol, ethanol, isopropyl alcohol, and tert-butyl alcohol in mixed hydroxylic solvents. A solution of the alkoxides of two alcohols in an excess of the two alcohols is allowed to react with n-butyl bromide to form a mixture of two ethers. The composition of the ether mixture is a measure of the "competitive reactivity" of thetwo alkoxides. This can be measured directly, and in theory can be factored into two components:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 1 publication
2
80
0
Order By: Relevance
“…5) was again below that of the ethanol-hydroxide shown in Fig. 6, because methanol has a higher acidity than ethanol [21], resulting in fewer hydroxide ions being available for saponification. As shown in Table 5, the apparent rate constants of the FAME saponification increased with increasing water content, e.g.…”
Section: Solutionmentioning
confidence: 88%
See 1 more Smart Citation
“…5) was again below that of the ethanol-hydroxide shown in Fig. 6, because methanol has a higher acidity than ethanol [21], resulting in fewer hydroxide ions being available for saponification. As shown in Table 5, the apparent rate constants of the FAME saponification increased with increasing water content, e.g.…”
Section: Solutionmentioning
confidence: 88%
“…The actual rate constants of the FAME saponification in the methanol-hydroxides were calculated based on the relative acidity of ethanol and methanol, e.g. methanol was 4.4 times more acidic than ethanol at 26°C [21]. The estimated relative apparent saponification rate constants of ethanol-hydroxides to methanol-hydroxides were 5.396, 5.423 and 6.938 at 40, 50 and 60°C, respectively.…”
Section: The Hydroxide-alkoxide Equilibrium For the Alcoholic Solutiomentioning
confidence: 99%
“…Reaction conversion increases with increasing basicity (entries 9–12; pK a of corresponding conjugate acids in water: HF, 3.2; HCO 3 − , 10.2; HPO 4 2− , 12.7; HO t Bu, 16.5). 16 Interestingly, the identity of the counter cation resulted in significant differences in conversion to the exhaustively coupled product, presumably due to differences in nucleophilicity (entries 13–14). 17 Lithium alkoxides were the only bases screened that favoured exhaustive coupling over selective coupling (entries 1, 15).…”
mentioning
confidence: 99%
“…For instance, the methyl phenylacetate yields were 64 %, 64 %, 67 %, 80 %, and 72 % at phenylacetonitrile/water/ethanol mole ratio of 1 : 7 : 53-1 : 33 : 45, respectively, showing the optimal phenylacetonitrile/water/ethanol mole ratio to be 1 : 13 : 51. Reeve et al (1979) reported that the relative acidity of methanol and ethanol were pH 4.4 and pH 1.0, respectively. Kamitanaka et al (2008) also reported that the concentration of alkoxide ion in methanol was much higher than that in ethanol, which might also be valid for the alcohols in the supercritical state, suggesting that the alkoxide ion concentration was responsible for the rapid formation of esters.…”
mentioning
confidence: 99%